The rise. 1968 - Leslie, Jay (New York : Franklin Watts, an imprint of Scholastic, Inc., 2023)
Explores the key events of the Civil Rights Movement, focusing on the year 1968, including the Memphis Worker's Strike, Arthur Ashe, the expansion of the Civil Rights Act of 1964 which implemented the Fair Housing Act, and more.
Introduction: The Way It Was -- A movement in Memphis -- One nation, two societies -- The view from the mountaintop -- The Civil Rights Act of 1968 -- Welcome to resurrection city -- The cost of Black Power -- Conclusion: The legacy of 1968 in civil rights history -- Biography: Charlene Mitchell -- Timeline.
Includes bibliographical references (page 92) and index.
6.8
5-8
1050L
Keywords: African Americans -- Civil rights -- History -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; Civil rights workers -- United States -- Juvenile literature; African Americans -- Civil rights -- History; Civil rights movements -- History -- 20th century; Civil rights workers